Fissures in algorithmic power: platforms, code, and contestation. - Ferrari, Fabian; Graham, Mark (Cultural Studies)
Digital labour platforms do not attempt to build trust between worker, client, and platform on the basis of strong and durable ties. Instead, platforms utilize a double articulation of algorithmic power to govern spatially dispersed workforces in both material and discursive ways. However, algorithms do not have hegemonic outcomes, and they do not entirely strip away agency from platform workers. Through manipulation, subversion, and disruption, workers bring fissures in algorithmic power into being. Fissures in algorithmic power are moments in which algorithms do not govern as intended. While these moments do not simply result in positive outcomes for workers, they show that algorithmic power is inherently only ever partial.